NEEDS ANALYSIS OF THE DEVELOPMENT OF SCHOOLOGY AND POWTOON-BASED LEARNING MEDIA TO INCREASE LEARNING MOTIVATION AND STUDENT LEARNING OUTCOMES - Deni Ainur Rokhim; Carlina Sukma Ayu Kurniawan; Qumillaylatul Ula; Imamul Huda Al Siddiq (Universitas Pendidikan Indonesia, 2022)
This article discusses the analysis of the need to develop learning media based on schoology and power to improve student motivation and learning outcomes. Student learning motivation will form motivation in achievement which is an effort to achieve the best learning outcomes that refer to the quality standards of education. Data collection techniques used are using open and closed questionnaires. The data obtained were analyzed using average calculations. The results of the study are teachers and students still using conventional learning materials and rarely use information and communication technology-based media that are more in demand by students. Thus it can be seen that overall development is still needed regarding the use of mediated based learning media especially in schoology and powtoon to stimulate students in increasing student motivation and learning outcomes